Pedological and ecological controls on biogenic silica cycling in grass dominated ecosystems - Melzer-Drinnen, Susan E., author; Kelly, Eugene F., advisor (Colorado State University. Libraries, 2009)
The biogeochemical behavior of silica is closely linked to the carbon cycle as marine Si-based diatoms are a major control on the distribution of silica in oceans, and play a major role in controlling atmospheric pCO2 via the "biological pump." The importance of biological controls on silica cycling in the terrestrial environment has only recently been known and our studies point to grasslands and grass dominated ecosystems as important repositories. Although the structure and ecological functioning of these ecosystems are strongly influenced by fire and grazing, the role of these key ecological drivers in the production and storage of Si represents a significant knowledge gap. Additionally, the effect of biogenic silica dissolution on the weathering of rock with different mineral assemblages is also insufficiently understood. I evaluated the effects of fire, grazing and parent material on the range and variability of plant derived biogenic silica stored in plant biomass and soils by sampling plants and soils in the mesic grasslands of North America and savannas of South Africa. Using these and other intensive study sites, along with extant productivity and soil texture data I estimated the global Si storage based on two approaches: "measure and multiply" and "paint by numbers".

Overall, our results indicate that South African plants and soils responded differently to ecological drivers with respect to Si cycling, and these are likely linked to differences in the age and evolutionary history of these ecosystems. Plants and soils from the grazed sites in the older South African ecosystems had up to 76% and 54% greater BSi totals, respectively, than grazed North American sites. In the North American soils, grazing and fire combined resulted in the greatest abundance of BSi, whereas South African soils had the highest biogenic silica in burned plots in the absence of grazing.

Our results also indicate that the cycling of Si is strongly influenced by parent material (and therefore, texture and soil hydrology). Fine textured basaltic soils had less total and dissolved Si with a greater proportion of the total Si made up of biogenic silica relative to coarse textured granitic soils. Additionally, plants and soils overlying basaltic parent material had greater abundance of biogenic silica and slower turnover times than those overlying granitic parent materials. While both basaltic and granitic soils were strongly regulated by biologic uptake, the former showed a "tighter cycle" with less loss of Si and the latter a "leakier cycle" which, although more dependent on biogenic silica dissolution, had greater losses of total Si.

A first order estimate of global average biogenic silica storage in the vegetation and underlying soils of grass dominated ecosystems worldwide indicated that Africa and Asia had the greatest stores of biogenic silica in both plant and soil which, was reflective of their larger grassland area. Europe had the lowest stores of plant and soil biogenic silica. Global average biogenic silica content for grassland aboveground biomass was -8 Tmole Si yr-1. Aboveground biomass BSi estimates for non-woody grasslands in North America alone was 0.315 (±0.002) Tmole Si yr-1. Global average biogenic silica content for grassland soils was -23,000 Tmole Si yr-1 which, was approximately 100-400 times greater than biogenic silica in all terrestrial aboveground biomass and approximately 3,000 times greater than global estimates for grasslands alone. Nonwoody North American grasslands had a biogenic silica content of -1,476 (±164) Tmol Si yr-1; however, 87% of this total resided within the fine size fraction and only 13% in the coarse size fraction. To extrapolate our results to continental scales we used simple regression models to predict plant and soil BSi using remotely sensed estimates of ANPP for the grass dominated ecosystems.

Overall, my data suggests that grass dominated ecosystems worldwide have the potential to accumulate high levels of biogenic silica due to the large quantities found in the dominant vegetation and soils and the lack of significant and continuous ground and stream water export pathways in these systems. These data were further utilized in conjunction with paleoenvironmental studies and ocean records to assess how major periods of grassland expansion and contraction may have influenced the terrestrial storage, mobilization and delivery of biogenic silica to the oceans. Although I was inconclusive in linking my data to the long-term temporal record in marine opal deposits, which is critical in interpreting the paleoclimate, I do speculate that during the late Miocene and onward, phytoliths contributed regularly to seawater chemistry, particularly during sea level falls as they are more labile sources of Si than mineral quartz.
Keywords: biogenic silica; grasslands; grazing; silica cycling; wildfires; ecology; biogeochemistry; soil sciences